The development of postverbal subjects in L2 Italian: A multifactorial corpus analysis - Listanti, Andrea; Torregrossa, Jacopo (Applied psycholinguistics, 2024)
Most studies on the acquisition of postverbal subjects (VS) in L2 Italian focus on a limited number of linguistic factors that tend to be associated with the production of VS in L1 (e.g., verb class and subject discourse status). Moreover, they analyze homogeneous groups of learners in terms of proficiency, mostly through controlled experiments. In this paper, we present a cross-sectional corpus study based on a multifactorial analysis of the L2 use of VS structures in semi-spontaneous speech. We analyze the production of VSs by learners of different levels of proficiency (A1-C2), considering linguistic factors that trigger the production of VS in L1, but have been unaccounted for in L2 studies (e.g., agentivity of the subject, syntactic configuration of the sentence, contrastive focus). We use a cumulative link mixed model to show how the features of verbs and subjects in VS structures change across proficiency levels. The results indicate learners’ progressive mastery of the mechanisms of assignment of the subject function to the postverbal constituent and increasing sensitivity to contrastive focus as a feature relevant for the use of VS. Furthermore, we observe that psychological verbs associated with the use of VS are produced from the earliest stages of L2 acquisition.